FORAMINIFERA ASSEMBLAGES AS A MARKER OF MUD ERUPTION SOURCE IN CIUYAH, CINIRU – KUNINGAN, WEST JAVA - Vijaya Isnaniawardhani; Faizal Muhamadsyah; Adjat Sudrajat (Indonesian Institute of Sciences, 2018)
Mud eruptions that rise claystone to sandstone-size fragments, liquid, gas, and heat to the surface have been identified in Ciuyah, Ciniru District, Kuningan. Field observation and sampling were conducted on host rock as well as mud in Ciuyah. Forty-two planktic and forty-two benthic foraminiferal species were identified in rock samples; while 89.28% of them are recorded in mud samples. Foraminifera contained in claystone and sandstone of Pemali and Halang Formations reveals the age of Middle to Late Miocene. Based on their stratigraphic ranges, planktic foraminifera assemblages in mud represent four age-marker groups, there are: older than Zone N.10 / Middle Miocene (indicated by the appearance of Globorotalia archeomenardii), ranges of Zone N.11 – N.12 / Middle Miocene (marked by the appearance of Globorotalia fohsi lobata and Globorotalia praemenardii), ranges of Zone N.13–N.14 / Middle Miocene (Globorotalia siakensis and Globorotalia mayeri), and ranges of Zone N.15–N.17 / Late Miocene (Globorotalia acostaensis acostaensis and Neogloboquadrina dutertrei dutertrei). Benthic foraminifera can be grouped into outer neritic and bathyal typical assemblages. That several age-marker planktic foraminifera groups mixing and deep marine typical benthic occurrence in mud samples is produced by reworking process during turbidity sedimentation, as well as erosion and elution of base- and side-rock composed by Pemali and Halang Formations.Semburan lumpur yang membawa fragmen-fragmen berukuran batulempung hingga batupasir, cairan, gas dan panas ke permukaan telah teridentifikasi di Ciuyah, Kecamatan Ciniru, Kuningan. Observasi lapangan dan pengambilan sampel dilakukan terhadap batuan induk serta lumpur di Ciuyah dan sekitarnya. Empat puluh dua spesies foraminifera planktik dan empat puluh dua spesies bentik teridentifikasi dalam sampel batuan; dengan 89,28% di antaranya terekam dalam sampel lumpur. Foraminifera yang terkandung dalam batulempung dan batupasir Formasi Pemali dan Halang menunjukkan umur Miosen Tengah hingga Akhir. Berdasarkan rentang stratigrafinya, kumpulan foraminifera planktik dalam lumpur menunjukkan empat kelompok penanda umur, yaitu: lebih tua dari Zona N.10 / Miosen Tengah (ditunjukkan oleh kehadiran Globorotalia archeomenardii), rentang Zona N.11 - N.12 / Miosen Tengah (ditandai oleh kehadiran Globorotalia fohsi lobata dan Globorotalia praemenardii), rentang Zona N.13 -N.14 / Miosen Tengah (Globorotalia siakensis dan Globorotalia mayeri), dan rentang Zona N.15 - N.17 / Miosen Akhir (Globorotalia acostaensis acostaensis dan Neogloboquadrina dutertrei dutertrei). Foraminifera bentik dapat dikelompokkan dalam kumpulan neritik luar dan batial. Beberapa kelompok penanda umur foraminifera planktik dan kehadiran bentik laut dalam pada lumpur dihasilkan oleh pengerjaan ulang selama sedimentasi turbidit, serta erosi dan elusi batuan dasar dan batuan samping yang tersusun oleh Formasi Pemali dan Halang.